2022
DOI: 10.3390/ijerph192114438
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure of Stabilizing Layers of Negatively Charged Silver Nanoparticles as an Effector of Shifts in Soil Bacterial Microbiome under Short-Term Exposure

Abstract: In this work, we have assessed the exposure of soil bacteria from potato monoculture to three types of silver nanoparticles (AgNPs) as well as silver ions (Ag+ ions) delivered in the form of silver nitrate and a commercially available fungicide. The diversity of the soil microbial community, enzymatic activity, and carbon source utilization were evaluated. It was found that only the fungicide significantly limited the abundance and activity of soil bacteria. Silver ions significantly reduced bacterial metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Hence, a possible mechanism of antibacterial activity is shown in Figure 8. Several recent studies reported and supported the antibacterial activity of synthesized AgNPs (Przemieniecki et al, 2022;Tripathi and Goshisht, 2022;Ivankovic et al, 2023).…”
Section: Evaluation Of Antibacterial Efficacymentioning
confidence: 78%
“…Hence, a possible mechanism of antibacterial activity is shown in Figure 8. Several recent studies reported and supported the antibacterial activity of synthesized AgNPs (Przemieniecki et al, 2022;Tripathi and Goshisht, 2022;Ivankovic et al, 2023).…”
Section: Evaluation Of Antibacterial Efficacymentioning
confidence: 78%
“…The silver ion's positive charge is assumed to be responsible for its antibacterial effect, as it attracts negatively charged microbes via electrostatic contact. This attraction is likely to outweigh other variables that influence bacterial cell death, such as size and shape [27].…”
Section: Discussionmentioning
confidence: 99%
“…The weight concentration of silver (Ag) nanoparticles in the solution after purification was evaluated by measuring the density of the native suspension ρ s and the effluent ρ e obtained following centrifugation. The mass concentration is then determined using the formula [ 54 ]: where: is the specific density of silver nanoparticles [ 55 ].…”
Section: Methodsmentioning
confidence: 99%